Knowledge, attitude and practices study on reproductive health among adolescent school students in a city of Central India - Baghel, Anil Singh; Chourasiya, Sanjay Kumar; Pal, Ravindra; Sharda, Ruchika (International Journal Of Community Medicine And Public Health, 2019)
Background: Ujjain is holy city of Lord Mahankal. It is an ancient city on the eastern bank of the Kshipra River. There were total 2508 students studying in 11th and 12th standards in various higher secondary schools of Ujjain city. Reproductive health is a crucial part of general health and a central feature of human development. It is a reflection of health during childhood and crucial during adolescence and adulthood, sets the stage for health beyond the reproductive years. Adolescence is a complex period of myriad of physiological as well psychological changes. This is a time for them to prepare for making responsibilities, a time of exploration and widening horizons and a time to ensure healthy all-around development. Adolescents lack knowledge regarding reproductive health problems. The present study is conducted to assess the knowledge, attitude and practices regarding selected aspects of reproductive health with special reference to knowledge of Reproductive tract infections (RTI) among adolescent school students. Methods: This was a cross sectional study carried out among randomly selected school students of Ujjain city. Results: It was observed that 86% of the students had adequate knowledge in the area of pregnancy and care during pregnancy. The mean score percentage of reproductive tract infection was found to be 56.92%. 90.50% students agreed that Menstruation is normal phenomenon. Conclusions: There is need of imparting sex education in schools across the country with the help of specially trained teachers and peer educators.